Financial Constraints and Investment Behavior in Low-Carbon Electricity Systems: An Agent-Based Analysis of Central Asia - Farida M. Tuleyeva; Saltanat S. Tamenova (Research Retrieval and Academic Letters, 2026)
The transition toward carbon-neutral electricity systems requires substantial investment, particularly in emerging regions with constrained financial markets. This study examines how financial constraints influence investment behavior in low-carbon electricity systems in Kazakhstan, Uzbekistan, and Kyrgyzstan. We develop the Heterogeneous Agent-Based Power Plant Investments (HAPPI) model, which simulates heterogeneous electricity producers making investment decisions under financial constraints, risk heterogeneity, and carbon price expectations. Results indicate that carbon pricing and subsidy reform significantly accelerate renewable energy deployment while increasing net public revenues. However, investment dynamics are strongly conditioned by financial constraints, with higher hurdle rates delaying low-carbon adoption. The findings highlight the importance of integrating financial mechanisms into energy policy design to ensure a fiscally sustainable and socially equitable transition